Discovery of mobocertinib, a potent, oral inhibitor of EGFR exon 20 insertion mutations in non–small cell lung cancer. (15th January 2023) - Huang, Wei-Sheng; Li, Feng; Gong, Yongjin; Zhang, Yun; Youngsaye, Willmen; Xu, Yongjin; Zhu, Xiaotian; Greenfield, Matthew T.; Kohlmann, Anna; Taslimi, Paul M.; Toms, Angela; Zech, Stephan G.; et al.
Graphical abstract: Abstract: In the treatment of non– small cell lung cancer (NSCLC), patients harboring exon 20 insertion mutations in the epidermal growth factor receptor ( EGFR ) gene ( EGFR ) have few effective therapies because this subset of mutants is generally resistant to most currently approved EGFR inhibitors. This report describes the structure-guided design of a novel series of potent, irreversible inhibitors of EGFR exon 20 insertion mutations, including the V769_D770insASV and D770_N771insSVD mutants. Extensive structure–activity relationship (SAR) studies led to the discovery of mobocertinib (compound 21c ), which inhibited growth of Ba/F3 cells expressing the ASV insertion with a half-maximal inhibitory concentration of 11 nM and with selectivity over wild-type EGFR. Daily oral administration of mobocertinib induced tumor regression in a Ba/F3 ASV xenograft mouse model at well-tolerated doses. Mobocertinib was approved in September 2021 for the treatment of adult patients with advanced NSCLC with EGFR exon 20 insertion mutations with progression on or after platinum-based chemotherapy.